The Probiotic Potential, Safety, and Immunomodulatory Properties of Levilactobacillus brevis ZG2488: A Novel Strain Isolated from Healthy Human Feces - Zhijie Cao; Mengshan Chen; Yulu Chen; Hui Sun (Fermentation)
Probiotics exert beneficial effects on health improvement, infection prevention, and disease management. This study investigated the probiotic characteristics and safety parameters of Levilactobacillus brevis ZG2488, a novel strain isolated from healthy human feces. The strain exhibited robust tolerance to simulated gastrointestinal conditions, maintaining survival rates of 87.20% in artificial gastric juice (pH 3.0; 3 h) and 95.32% in 0.3% bile salt (24 h). Notably, L. brevis ZG2488 displayed superior microbial adhesion properties with high cell surface hydrophobicity (87.32%), auto-aggregation (81.15% at 24 h), and co-aggregation capacities with Escherichia coli ATCC 43895 (63.90%) and Salmonella typhimurium SL1344 (59.28%). Its adhesion to HT-29 cells (7.15%) surpassed that of the reference strain Lactobacillus rhamnosus GG (1.26%). Antimicrobial testing revealed broad-spectrum inhibitory effects against multidrug-resistant Klebsiella pneumoniae NK04152 and other pathogens. Comprehensive safety assessments confirmed the absence of hemolytic or DNase activity, along with appropriate antibiotic susceptibility to most antibiotics, except kanamycin, streptomycin, vancomycin, and penicillin G. Furthermore, L. brevis ZG2488 significantly enhanced nitric oxide production and upregulated the gene expression of nitric oxide synthase (iNOS) and proinflammatory cytokines (IL-1β, IL-6, and TNF-α) in RAW264.7 macrophages. These findings underscore L. brevis ZG2488 as a promising probiotic candidate with functionality in pathogen inhibition and immune modulation.